THE ACCURACY OF REFERENCES IN MANUSCRIPTS SELECTED FOR PUBLICATION IN PAKISTAN ARMED FORCES MEDICAL JOURNAL (PAFMJ): Accuracy of References in Manuscrips - Ullah, Midrar; Butt, Idrees Farooq; Mubarik, Azhar (Pakistan Armed Forces Medical Journal, 2008)
Objective: To assess the accuracy of references cited in manuscripts accepted for publication in an issue of a scientific journal and to categorize these errors. Design: An observational study. Place and duration: The study was conducted in the library of Army Medical College, Rawalpindi during September 2007. Materials and Methods: A total of 288 references listed in the references section of twenty manuscripts were examined. Journal references were compared with either the original articles or abstract obtained through MEDLINE and Pakmedinet. Book references were checked against the original book or bibliographical information obtained through Publisher’s catalogues and online catalogues of libraries. The total number of errors in the references were counted and categorized. Results: Seventy (24.3%) of the 288 assessed references had no errors, while a single error occurred in 51(17.7%) and more than six errors were found in 22(7.64%) references. The author element was the most frequent error category, where 103(43.64%) references from journal and 26(63.41%) references from books contained the errors. Conclusion: The primary responsibility of ensuring accuracy of references lies with the authors. However the continuous process of removing errors by reviewers and editorial team can reduce the error rate in the references.